New Forms of Consecrated Life (C. 605 CIC & C. 571 CCEO) With Particular Reference to Ashrams - Anthonappa, Jerome R. (2015)
571 CCEO
Keywords: Katholische Kirche; Ordensleben; Evangelische Räte; Ordensinstitut